TYPES OF QUESTIONS USED BY THE TEACHERS AND STUDENTS’ RESPONSES IN ENGLISH TEACHING LEARNING PROCESS OF GRADE XI AT SMA FREE METHODIST 2 MEDAN - Widya Kristina Manalu; Nora Ronita Dewi (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
This research aims to answer the three problem questions of this research, they are about types of questions are used by English teachers in teaching reading skill, teachers’ purposes in asking questions and students’ responses to the teachers’ questions. This research was conducted at SMA Free Methodist 2 Medan. The method of the study is qualitative descriptive, the subjects of this study were two english teachers and two classes of Grade XI at SMA Free Methodist 2 Medan. The data were collected by doing observation to the classroom, interview to the two English teachers, and record English teaching learning process. The result of this study showed that the two English Teachers in SMA Free Methodist 2 Medan commonly used all types of question in teaching reading skill, they are Question of Literal Comprehension, Question of Involving Reorganization or Interpretation, Question of Inference, Question of Evaluation, Question of Personal Response. After the reseacher analyzed the both teachers mostly used Question of Inference. The researcher also collect data about teachers’ purposes in asking the question to the students. Teacher 1 said his purpose is to know students’ understanding and Teacher 2 said that his purpose is involving students in teaching learning process. The researcher also analyzed students’ responses in two classes of grade XI, they are XI IPA 2 and XI IPS 2. The way teachers asked student in giving responses is by calling students’ name, pointing students and just a little raising hand. Only some students were active in giving responses even though in English or Bahasa Indonesia, those mostly used cognitive in answering the question from teachers.Key words: Teachers’ Questions, Students’ Responses, Reading Skill